Analyzing Components of Productivity Growth Using the Bennet-Lowe Indicator: An Application to Welsh Sheep Farms. (15th March 2019) - Ang, Frederic
Abstract: This article introduces the Bennet-Lowe Total Factor Productivity (TFP) indicator. The proposed measure is difference-based, additively complete, and transitive. We also develop a general nonparametric framework to exhaustively decompose all Bennet-type TFP indicators, including the one introduced here, into technical change, technical efficiency change, scale efficiency change, and mix efficiency change. This decomposition provides a powerful tool for policy makers to guide financial decisions on research and development, extension, subsidies, and price support. The empirical application focuses on the Welsh sheep sector for the years 2001–2014. The results show that in this 14-year period, Welsh sheep farms increased their TFP by 30.28% on average (2.33% p.a.). However, the exhaustive decomposition shows that TFP growth is not distributed equally across all farms, with an increasing divergence between front-runners and laggards. The negative values of scale efficiency change and mix efficiency change cast doubt on the current subsidy policies.